Low-Temperature Dried Alginate/Silica Hybrid Aerogel Beads with Tunable Surface Functionalities for Removal of Lead Ions from Water - Jiuqi Wei; Shilong Yang; Zhicheng Zhu; Jialu Lu; Bencong Zhang; Mingmei Zhang; Wei Wei (Gels, 2025)
Low-temperature dried alginate/silica hybrid aerogel beads with a large specific surface area (160.8 m2/g), low density (0.160 m2/g), and high degree of sphericity were successfully fabricated. Single networks of silica aerogels beads were synthesized via by calcining hybrid aerogel beads in air. Moreover, alginate-derived carbon/silica aerogel beads were also obtained by the thermal treatment of the hybrid aerogel beads in nitrogen, which were indicative of the double networks of the as-synthesized crack-free hybrid aerogel beads for the first time. The adsorption performances of above aerogel beads were also investigated. Meanwhile, using a common silane coupling agent as a modifying agent, a series of hybrid aerogel beads with tunable functional surfaces were obtained. The results showed that the obtained samples adsorbed Pb2+ well, and the hybrid aerogel beads modified with KH-590 exhibited an experimental maximum adsorption capacity of Pb2+ of 193.73 mg·g−1.